Desvendando a relação estrutura-função de condroitim sulfatos : estudo de efeitos anti-inflamatórios sobre condrócitos e macrófagos - Cunha, Andre Luiz da [UNIFESP] (2017)
The aim of the present study was to investigate the activities of chondroitin sulfates (CS) with different structures on cultured chondrocytes and macrophages. CS were extracted and purified from bovine trachea (CSTB), porcine trachea (CSTS), chicken sternum (CSFr) and skate (CSRj) cartilage. The preparations were 90-98% pure, with ~1% proteins, nucleic acids and keratan sulfate contaminants. Structural analysis of these CS and of commercial C4S and C6S has shown that most of their disaccharides are monosulfated: C4S, CSTB, CSTS and CSFr are predominantly 4-sulfated (64-78%), while C6S is more 6-sulfated (71%) and CSRj is more heterogenous. All the CS showed minor ammounts of non-sulfated disaccharides (2-7%), and 2,6-disulfated disaccharides were detected in C6S (7%) and CSRj (14%). All CS were polydisperse, with modal molecular weights of 26-135 kDa. The different CS reduced the IL-1β-induced liberation of NO and PGE2 on both human and horse chondrocytes, and CSTB was the most effective. C4S, C6S, CSFr and CSRj reduced the LPS-induced TNF-α liberation, but not IL-6, on RAW 264.7 immortalized macrophage-like cell line. In contrast, on bone marrow derived macrophages (primary culture), C4S, C6S, CSTB and CSTS reduced the LPS-induced liberation of TNF-α, IL-6, IL-1β, and NO, indicating that the RAW response to CS was different from that of primary macrophages. All CS, except for commercial C4S, inhibited the translocation of NF-κB transcription factor to the nucleus of LPS-challenged bone marrow derived macrophages. In conclusion, our results have shown that CS with different structures had anti-inflammatory effects on macrophages, besides the already known effects on chondrocytes, suggesting that, in vivo, a synergic action of these molecules on different cell types help to achieve its desired therapeutic effects.